Personal data protection and the right to privacy on social media / Lim Jing Xie and Nabila Ayuni Abdul Malek - Lim, Jing Xie; Abdul Malek, Nabila Ayuni (UiTM Cawangan Negeri Sembilan, 2022)
The generation today, especially post COVID-19 era, tend to spend most of the time online. The use of social media has spiked tremendously over the years, leading to alarming concerns about data breaches online. The intersection between privacy and cybersecurity leads to many concerns among internet users. In the year 2020, there have been plans by the Ministry of Communications and Multimedia (KKMM) to discuss possible amendments to the Personal Data Protection Act 2010 (PDPA) after identifying gaps and lacuna within the PDPA when compared to personal data legislation with other ASEAN countries. With this recognition, there have been calls for the attention for the protection, where Judge Cooley calls 'the right to be left alone'. Privacy refers to 'the condition or state of being free from public attention to intrusion into or interference with one's acts or decisions'. It is one of the values flowing from the principles of human dignity and autonomy. Data privacy is the protection of personal data from those who should not have access to it and the ability of individuals to determine who can access their personal information.